Penyuluhan dan Pemanfaatan Lahan Bengkok Untuk Budidaya Tanaman Cabai Rawit di Desa Cipinang: - Chindy Maelani Devi; Sandi Nasrudin Wibowo (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
One area with a large enough land area is Cipinang Village, Beber District, Cirebon Regency. However, as development progresses, Cipinang Village is getting denser over time, and less area will be used for agricultural land. The more the population increases, the greater the demand for food. In order to meet the growing family food supply, every household should have one or more food crops or vegetables for consumption. Therefore, it is necessary to hold outreach activities to the community about the use of narrow land for the cultivation of food crops and vegetables. The purpose of this service is to provide awareness to the community about the importance of utilizing land as well as good cultivation practices based on lectures. The method used is socialization and demonstration plots starting from nurseries to transplanting. The targets of this counseling are housewives and the Cipinang village community. The extension workers in this case are KKN students who carry out counseling and chili planting practices by utilizing village land (Bengkok). The output of this activity is expected that the community can absorb knowledge and practice cayenne pepper planting activities in their yards in order to create food self-sufficiency.